EFEKTIVITAS PEMBIAYAAN AKAD MURABAHAH DALAM PEMBIAYAAN BAITUL MAAL WAT TAMWIL (BMT) TERHADAP MASYARAKAT MISKIN - fajrianti, vira (IAIN Parepare, 2024)
BMT is a sharia financial institution that is oriented towards mutual benefits, with the principles of profit sharing, buying and selling, non-profit, partnership agreements and financing based on agreements. The financing provided by BMT aims to improve the community's economy, provide funds for the business world, and distribute income. One of the financing concepts used is Murabahah, a form of sales where the bank acts as the seller and the customer as the buyer